(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2025)
This study evaluated a teaching strategy for the development of logical-verbal memory in the systematization of basic multiplication exercises. Through a pedagogical quasi-experiment with 58 third-grade students (Camagüey, Cuba), consisting of 15 sessions, an experimental intervention (n=31) that integrated multisensory representations, guided verbalization of mathematical properties, and progressive metacognitive scaffolding was compared with rote methods of repetition of multiplication tables (n=27, control group). The results show a significant superiority of the experimental group in the following dimensions: semantic-conceptual (87,1 % vs. 55,6 %; p=0,009), procedural-regulative (80,6 % vs. 48,1 %; p=0,013), and socio-affective-evaluative (93,5 % vs. 63 %; p=0,008). The strategy demonstrated that logical-verbal memory, operationalized as self-correcting fluency, transforms the exercise into an activity of reconstructing meanings.